ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN: STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013 - Jessika Zarlia (Jurnal Manajemen, 2014)
This research aims to get empirical evidence about Corporate Social Responsibility (CSR) and profitability that influence firm value in simultan and partial. The exposure of CSR is measured based on Sustainability Reporting Guidelines (SRG) that is published by Global Reporting Initiative (GRI). Profitability is measured by Return on Assets (ROA). Firm value is measured by Tobin’s Q ratio. This research takes 64 manufacturing company that is listed at Bursa Efek Indonesia (BEI) 2013 from purposive sampling method. This research use multiple regression analysis. The result indicates that there is a positive influence of CSR and profitability to firm value in simultan and partial